Stumpage Prices in Sweden 1909-2011: Testing for Non-Stationarity - Linda Andersson; Lars Hultkrantz; Panagiotis Mantalos (Örebro University School of Business, 2013)
The price of timber stumpage is one of the few natural-resource rents that can be directly observed as a market price. Rules for optimal timber harvesting under uncertainty have been found to depend on whether the timber rent price is non-stationary or stationary. In this study we extend previous research by Hultkrantz (1995) that tested for unit-root with an exogenous break point in Swedish stumpage prices from 1909-1990, employing data up to 2011, hence for 103 years, and unit-root tests with an endogenously selected break point. We find support for a structural level break at the end of WW2 and that non-stationarity can be rejected. We show that this is a robust conclusion.
Keywords: Q23; 330; Roundwood; timber; natural-resource rents; unit root